Rola dziegciu i kory w zdobnictwie naczyń neolitycznych. Lingwistyczny przyczynek do prahistorii estetyki - Kowalski, Andrzej P. (Wydawnictwo Naukowe UAM, 2003)
The article presents hypothetical interpretation of expressions connected with the use of tar and bark in the decoration of Central European Neolithic vessels. The data of Indoeuropean linguistics make it possible to discern sources of important aesthetic categories in reference to the methods of bark working and use. Some traditional expressions of beauty and grace derive from the names of techniques of vegetable dye use and from birch tar glossiness. The linguistic evidence presented above gives an empirical support to archaeological observations. It constitutes the basis of “genealogical” analysis in which prehistory of production is treated as a culture-practical context of formation of later aesthetic categories.
Importance of birch tar and bark in the decoration of neolithic vessels. A linguistic contribution to the prehistory of aesthetics